La construcción del discurso homofóbico en la Europa cristiana medieval - Bazán, Iñaki (En la España Medieval, 2007)
This article reviews and analyzes the different factors that contributed to the construction of a homophobic discourse in European society beginning in the thirteenth century. Attention particularly centers upon masculine homosexuality.